2017
DOI: 10.1371/journal.pone.0177786
|View full text |Cite
|
Sign up to set email alerts
|

Comparative lytic efficacy of rt-PA and ultrasound in porcine versus human clots

Abstract: IntroductionPorcine thrombi are employed routinely in preclinical models of ischemic stroke. In this study, we examined the differential lytic susceptibility of porcine and human whole blood clots with and without the use of microbubbles and ultrasound (US) as an adjuvant.Materials and methodsAn in vitro system equipped with time-lapse microscopy was used to evaluate recombinant tissue-plasminogen activator (rt-PA) lysis of porcine and human clots in the same species or cross species plasma. Human and porcine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 73 publications
2
17
0
Order By: Relevance
“…Furthermore, plasma was found to contain endogenous t-PA, which was likely responsible for the observed lysis (Jern et al 1997). However, the amount of plasminogen was reported to be substantially lower in porcine clots and porcine plasma compared to human clots and human plasma, which resulted in lower porcine clot mass loss measurements (Flight et al 2006; Huang et al 2017, Lewis 1996). The clot mass loss of mildly retracted and highly retracted porcine clots after treatment with rt-PA was significantly higher than that obtained in the plasma alone arm (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, plasma was found to contain endogenous t-PA, which was likely responsible for the observed lysis (Jern et al 1997). However, the amount of plasminogen was reported to be substantially lower in porcine clots and porcine plasma compared to human clots and human plasma, which resulted in lower porcine clot mass loss measurements (Flight et al 2006; Huang et al 2017, Lewis 1996). The clot mass loss of mildly retracted and highly retracted porcine clots after treatment with rt-PA was significantly higher than that obtained in the plasma alone arm (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…2 and 3) were consistent with these earlier findings. Porcine clots have been reported to be less susceptible to rt-PA lysis due to their lower activation of porcine plasminogen by rt-PA, along with the denser fibrin network and thinner fibrin fibers in porcine clots than those in human clots (Flight et al 2006; Landskroner et al 2005; Huang et al 2017). In addition, clots with denser fibrin network and thinner fibers were found to be stiffer than those with more porous network and thicker fibrin fibers (Li et al 2016; Wufsus et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that sonothrombolysis can enable a reduction in the quantity of drug required. The drug alone did not produce significant lysis, which is attributable to the relatively short time frame of the experiment (60 min), the low concentration of tPA (0.75 mg/mL) compared with clinical doses and the use of porcine blood and plasma (Huang et al 2017). Even under these conditions, substantial lysis acceleration occurred with US and non-targeted microbubbles.…”
Section: Discussionmentioning
confidence: 94%
“…To further increase clinical relevance, the composition of the plasma solution in the flow loop may also be improved. A recent study by Huang et al (2017) reported that using human plasminogen in the liquid surrounding a porcine clot produces sonothrombolysis behaviours that more closely resemble human clots in human plasma.…”
Section: Limitationsmentioning
confidence: 99%
“…However, gas pockets stabilized by a monolayer within the liposome, or within the bilayer shell are hypothesized to be responsible for the echogenicity of these vesicles 31 . We have also demonstrated 120-kHz US-enhanced thrombolysis in the presence of rt-PA and Definity (Lantheus Medical Imaging, North Billerica, MA), an FDA approved contrast agent 32,33 . Stable cavitation and acoustic radiation force were identified as the mechanisms for the lytic enhancement 22,32 .…”
Section: Introductionmentioning
confidence: 99%